Swimming against the tide: investigations of the C-bouton synapse - Deardorff, Adam S.; Romer, Shannon H.; Sonner, Patrick M.; Fyffe, Robert E. W. (Frontiers in Neural Circuits, 2014)
C-boutons are important cholinergic modulatory loci for state-dependent alterations in motoneuron firing rate. Type 2 muscarinic acetylcholine (m2) receptors are concentrated postsynaptic to C-boutons, and m2 receptor activation increases motoneuron excitability by reducing the action potential afterhyperpolarization (AHP). Here, using an intensive review of the current literature as well as data from our laboratory, we illustrate that C-bouton postsynaptic sites comprise a unique structural/functional domain containing appropriate cellular machinery (a ‘signaling ensemble’) for cholinergic regulation of outward K+ currents. Moreover, synaptic reorganization at these critical sites has been observed in a variety of pathologic states. Yet despite recent advances, there are still great challenges for understanding the role of C-bouton regulation and dysregulation in human health and disease. The development of new therapeutic interventions for devastating neurological conditions will rely on a complete understanding of the molecular mechanisms that underlie these complex synapses. Therefore, to close this review, we propose a comprehensive hypothetical mechanism for the cholinergic modification of α-MN excitability at C-bouton synapses, based on findings in several well-characterized neuronal systems.